Projection and Visualization of Health Worker Data in Indonesia (2015–2017) Using Google Looker Studio - Prasiwiningrum, Elyandri (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Projection of health worker data in Indonesia during 2015–2017 highlights the need for efficient workforce planning to address rising healthcare demands. This study examines the distribution and projection of ten healthcare professions, including nurses, midwives, pharmacists, and general practitioners, using Google Looker Studio for visualization. Secondary data analysis was utilized to process information obtained from credible sources, ensuring relevance and accuracy. The challenge lies in understanding workforce disparities and predicting future needs to optimize hospital operations effectively. Google Looker Studio was employed to create interactive dashboards, simplifying data interpretation and enhancing decision-making capabilities. Results indicate a continuous increase in healthcare personnel over time, with 2,172 professionals recorded during the observed period. Visualization provides insights into workload distribution and the adequacy of healthcare workers across regions. This research offers a scalable solution for projecting workforce trends and supports long-term healthcare planning in Indonesia